We want to use elimination to solve
y = 0 (1)
x + y = 40 (2)
Multiply (1) by -1 to eliminate y.
-y = 0 (3)
Add (2) and (3).
x + y + (-y) = 40 + 0
x = 40
Answer: Multiply by -1.
Answer:
the answer is 36 gallon
Step-by-step explanation:
#4(1)=-1. (2)=5. (3)=14. (4)=26 srry but all i know hoped i helped
[how i did]
the first one i did 3×-5+14 which equals -1
and the second one is the same two 3×-3+14=5 you just add the the number on B
C = (pi) * d
C / (pi) = d
30 / 3.14 = d
9.55 = d
Answer:
ooooooooooooooooooooooooooooooooo
Step-by-step explanation:
la de da de da la de da de deee sudennly you call my name an I lose my weight and I float up to the sky!